Associationalism Canadian Style: Flour Millers, Self-Regulation and the State, 1920-1935 - Cox, Mark (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
AbstractBetween the two world wars, the expansion of the state's regulatory capacity caused business-state relations in Canada to worsen rather than improve, as large manufacturers and those in government who advocated regulation viewed the utility of state power in different, and largely incompatible ways.The Canadian flour milling industry illustrates these persistent tensions. Confronted by overcapacity and seeking a method of coordination, the large millers organized an association in 1920. It established a complex system of regulations to fix prices. However, it initially failed completely to control either export or domestic prices and, when it finally seemed to have exerted greater control over domestic prices in 1930, the federal Combines Investigation Branch responded by forcing the suspension of price-fixing, just when market conditions reached a nadir. Numerous efforts to reorganize the industry through consolidations all failed. Late in 1933, the large millers sought state assistance to secure stability, but the solutions proposed would have imposed unwanted constraints on their power within the industry. Hence, the large millers did all they could to frustrate the development of regulation, continuing to advocate voluntary associationalism despite its past failures.The fundamental differences between the large millers and government over the function of regulation prevented the consensus necessary to make a regulatory solution work. This suggests that, whereas the regulation of community property succeeded because it accommodated interests and defrayed tensions, the process through which it acquired broad legitimacy did not extend to the regulation of private property. Indeed, without consensus that such regulation was desirable, attempts to create it produced conflict instead of accommodation.